Challenges Encountered by School Administrators During the New Normal Education: A Phenomenological Study - Haydee D. Villanueva; Jujie A. Buenbrazo (EduLine: Journal of Education and Learning Innovation, 2023)
The new normal education poses a great challenge to learners, parents, and other stakeholders and, more importantly, school administrators in delivering the new learning modality. This study explored the challenges encountered by administrators of integrated schools in the Division of Ozamiz City during the School Year 2021-2022. The phenomenological research design was used in the study, with nine school administrators as the participants selected through purposive sampling. An Interview Guide was used in gathering the data through face-to-face and virtual interviews. The Moustakas’ steps for data analysis were used in analyzing the data gathered. Results revealed four themes: lack of school preparedness for the new modality; difficulty in soliciting parents’ cooperation and involvement; communication and monitoring barriers; and the uncertainty of the effectiveness of modular distance learning. The study concludes that implementing the new normal education posed several challenges to school administrators as one of the forerunners of the new learning modality.